Examining The Inclusion of Persons with Visual Impairment in The Formal Employment Sector in Uganda - Niyisabwa, Odette Tumwesigye; Emong, Paul (PLD UIN Sunan Kalijaga, 2024)
This article examines the inclusion of persons with visual impairments (PwVIs) in the formal employment sector in Uganda. It examines their experiences while searching for jobs, the attitudes of employers towards their employment, and their working conditions. The article is based on research on access to and retention of PwVIs in formal employment in Uganda. The research was examined within the theoretical perspectives of disability as a social model and human rights issues. A qualitative research design using a phenomenological approach was applied to obtain information through interviews. Ten employees with visual impairment in the formal employment sector were possessively selected. Results indicated that employers did not have enough knowledge and specialized manpower to employ PwVI. They also lacked reasonable accommodation provisions for employees with visual impairment. In addition, employers had negative attitudes towards PwVI, which led to discrimination, exploitation, abuse, and humiliation. Artikel ini meneliti inklusifitas bagi penyandang disabilitas netra di sektor ketenagakerjaan formal di Uganda. Artikel ini meneliti pengalaman mereka saat mencari pekerjaan, sikap penyedia kerja terhadap pekerjaan mereka, dan kondisi kerja mereka. Artikel ini didasarkan pada penelitian tentang akses dan retensi penyandang disabilitas netra di sektor ketenagakerjaan formal di Uganda. Penelitian ini diperiksa dalam perspektif teoritis tentang disabilitas sebagai model sosial dan isu-isu hak asasi manusia. Desain penelitian kualitatif menggunakan pendekatan fenomenologis diterapkan untuk mendapatkan informasi melalui wawancara. Sepuluh karyawan dengan disabilitas netra di sektor ketenagakerjaan formal dipilih secara positif. Hasil menunjukkan bahwa penyedia kerja tidak memiliki pengetahuan terkait ketenagakerjaan disabilitas yang cukup untuk mempekerjakan Penyandang disabilitas netra. Mereka juga tidak memiliki ketentuan akomodasi yang layak untuk karyawan dengan disabilitas netra. Selain itu, penyedia kerja memiliki sikap negatif terhadap penyandang disabilitas netra, yang mengarah pada diskriminasi, eksploitasi, penyalahgunaan, dan penghinaan.